(untitled) (ELang | An English Language Education Journal, 2018)
The research investigated “Teaching Reading Comprehension Through Jigsaw Technique” for the seconds grade students of SMP Negeri 3 Cidaun in Jl. Patriot no 10 Cimaragang, Cidaun, Cianjur in the academic year 2019/2020. The aims of the research are to know the significant difference in the result of jigsaw technique and the conventional technique in teaching narrative reading text, and to know the effectiveness by using jigsaw technique in teaching narrative reading text. A quasi experimental design was use to conduct the research. The population of this study was the second grade students of SMP Negeri 3 Cidaun in Cidaun,Cianjur. The sample of this study was 50 students. It was divided into groups. Twenty five students were as experimental group and twenty five were as control group. The experimental group was given the treatment by using jigsaw technique. The researcher gave the test, those were pre-test and post-test. The research finding showed that jigsaw technique is effective. It can be seen from the result after the treatments, t obtained is 9.353. the result of t-table is 2.021 the t-test value is bigger than that of t-table (9.353 > 2.021). It means that jigsaw technique as a technique of teaching narrative reading text to the seconds grade students of SMP Negeri 3 Cidaun in Cidaun, Cianjur has significantly better result than that of the conventional technique. It means that this technique is effective. The writer suggest that the English teacher should apply jigsaw technique in teaching reading, especially in teaching narrative reading text. Keywords: Reading Comprehension, Jigsaw Technique